Form-Meaning Relations in Russian Confirmative and Surprise Declarative Questions - Munteanu, Andrei; Kiss, Angelika (Language and speech, 2025)
Declarative questions (DQs) are declarative sentences used as questions. As declaratives, they differ from information-seeking polar questions (ISQs) in their syntax, and as biased questions, they differ from polar questions because they can convey various epistemic stances: a request for confirmation, surprise, or incredulity. Most studies on their intonation typically compare just one subtype to ISQs. In this paper, we present a production study where participants pronounced ISQs, confirmative and surprise DQs, and assertions in Russian. We analyzed the pitch and duration of the target utterances, as these prosodic cues proved to be important in the formal markedness of various biased question types across languages. A principal component analysis (PCA) on the pitch contours shows that DQs bear the same rise-fall contour as ISQs, but its peak falls on the stressed syllable of the last word of the sentence instead of the verb. The intonation of surprise DQs differs from that of confirmative ones in that they also exhibit a slight peak on the subject. Pitch alone is thus enough to distinguish the four utterance types tested. The PCA analysis was also used to identify higher-level trends in the data (principal components), two of which appear to correspond to core semantic properties, namely belief change and commitment. In addition to intonation, speaker commitment also correlates with utterance duration.